2008
DOI: 10.1007/s10863-008-9144-z
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the structure of human VDAC1, a key molecule in mitochondrial cross-talk

Abstract: The voltage dependent anion-channel, VDAC, is the major constitutive protein of the outer membrane of mitochondria. Functionally, VDAC is involved in the exchange of small metabolites over the mitochondrial outer membrane and supports enzymes of the cytoplasm with energy precursors i.e. ATP. Moreover, the channel alone or in complex with proteins of the inner mitochondrial membrane or the intermembrane space provides a basis for docking of cytosolic proteins which can regulate outer membrane permeability in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In addition, as more membrane bound β-barrel crystal structures are determined, exceptions to the list of 10 explicit rules governing porin structure, as outlined by Schulz [12], are found. For example, in recent structures for mitochondrial protein VDAC, the β-barrel is comprised of 19 β-strands (2JK4) [45], [46], where it was previously considered that β-barrels were comprised solely of an even number of strands. In another recent structure, the barrel is made up of 3 subunits, each making up 4 strands of the 12-stranded barrel [47], illustrating another unique barrel fold.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as more membrane bound β-barrel crystal structures are determined, exceptions to the list of 10 explicit rules governing porin structure, as outlined by Schulz [12], are found. For example, in recent structures for mitochondrial protein VDAC, the β-barrel is comprised of 19 β-strands (2JK4) [45], [46], where it was previously considered that β-barrels were comprised solely of an even number of strands. In another recent structure, the barrel is made up of 3 subunits, each making up 4 strands of the 12-stranded barrel [47], illustrating another unique barrel fold.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the formation of a large channel comprising VDAC1 monomers and serving as the Cyto c release channel has been proposed [5,154,155,193,[223][224][225]. Substantial evidence supports the claim that VDAC1 can exist as higher-order oligomers, namely as monomers, dimers, trimers, tetramers, and hexamers, with the formation of higher ordered VDAC1-containing complexes having been demonstrated [154,155,193,195,[230][231][232][233]. In several studies, it has been reported that both purified soluble and membrane-embedded VDAC1 can assemble into dimers, trimers and tetramers in a dynamic process [234].…”
Section: A Vdac1 Oligomeric Structure As a Cyto C Release Pathwaymentioning
confidence: 98%
“…However, recent studies demonstrated that VDAC1 over-expression is accompanying by its oligomerization (Zalk et al, 2005; Goncalves et al, 2007; Hoogenboom et al, 2007; Malia and Wagner, 2007; Shoshan-Barmatz et al, 2008a,b; Zeth et al, 2008; Keinan et al, 2010). VDAC1 has been shown to form different oligomeric states, namely monomers, dimers, trimers, tetramers, hexamers, and higher-order oligomers (see VDAC1 Oligomerization and Function).…”
Section: Vdac1 Expression Levels In Healthy and Cancer Cellsmentioning
confidence: 99%